1994
DOI: 10.1148/radiology.193.1.8090902
|View full text |Cite
|
Sign up to set email alerts
|

Os acromiale associated with rotator cuff impingement: MR imaging of the shoulder.

Abstract: Os acromiale can be an important cause of rotator cuff impingement and can be detected with routine MR imaging of the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 0 publications
1
40
1
1
Order By: Relevance
“…The os acromiale is an accessory ossicle between the lateral aspect of the clavicle and the acromial process of the scapula [1,2,17,18,19,20,21]. It has a reported prevalence of 1-15% [2,17,18], may be bilateral in up to 62% of cases [17], and is more frequent in men and black individuals [17].…”
Section: Os Acromialementioning
confidence: 99%
See 2 more Smart Citations
“…The os acromiale is an accessory ossicle between the lateral aspect of the clavicle and the acromial process of the scapula [1,2,17,18,19,20,21]. It has a reported prevalence of 1-15% [2,17,18], may be bilateral in up to 62% of cases [17], and is more frequent in men and black individuals [17].…”
Section: Os Acromialementioning
confidence: 99%
“…It has a reported prevalence of 1-15% [2,17,18], may be bilateral in up to 62% of cases [17], and is more frequent in men and black individuals [17]. It has been traditionally interpreted as an unfused acromial apophysis in the skeletally mature individual [2,18,19], although this has been disputed [17]. The shape and size of the os acromiale may vary, as well as its link with the rest of the acromion, which may be formed by a synovial articulation (Fig.…”
Section: Os Acromialementioning
confidence: 99%
See 1 more Smart Citation
“…Os acromiale is quite apparent on axial radiographs (Liberson 1937), in CT (Grasso 1992) and MRI (Park et al 1994). Recently, Gumina et al (2003) reported that in most patients with os acromiale the distance of the acromioclavicular AC joint to the anterior edge of the acromion is larger than in a normal population, and described 3 types of relationship between os acromiale and the AC joint.…”
mentioning
confidence: 99%
“…It is usually associated with subacromial impingement (Hutchinson andVeenstra 1993, Jerosch et al 1994) or rotator cuff tears (Mudge et al 1984, Park et al 1994, Boehm et al 2003. Mudge et al (1984) have been the only authors to report the incidence of os acromiale in patients with rotator cuff tears, and found 9 os acromiale in 145 patients (6%).…”
mentioning
confidence: 99%